2013
DOI: 10.1056/nejmoa1213277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Remission-Induction Regimens for ANCA-Associated Vasculitis

Abstract: Background The 18-month efficacy of a single course of rituximab as compared with conventional immunosuppression with cyclophosphamide followed by azathioprine in patients with severe (organ-threatening) antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis is unknown. Methods In a multicenter, randomized, double-blind, double-dummy, noninferiority trial, we compared rituximab (375 mg per square meter of body-surface area administered once a week for 4 weeks) followed by placebo with cyclophospham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
466
3
28

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(536 citation statements)
references
References 34 publications
(45 reference statements)
11
466
3
28
Order By: Relevance
“…Although the population was heterogeneous, it reflects the features of patients from real life with baseline BVAS and clinical manifestations similar to those observed in patients included in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial (20,21). The findings of our study strongly suggest that IVIG exhibits overall efficacy, with an acceptable safety profile and with remission rates at 12 months that are comparable to those observed in the RAVE trial (20,21). …”
Section: Discussionsupporting
confidence: 54%
“…Although the population was heterogeneous, it reflects the features of patients from real life with baseline BVAS and clinical manifestations similar to those observed in patients included in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial (20,21). The findings of our study strongly suggest that IVIG exhibits overall efficacy, with an acceptable safety profile and with remission rates at 12 months that are comparable to those observed in the RAVE trial (20,21). …”
Section: Discussionsupporting
confidence: 54%
“…Rituximab met criterion for noninferiority; 64% of patients reached the primary endpoint compared with 53% in the CYC group (P,0.001). Longer follow-up of the RAVE trial found sustained remission rates of 48% and 39% with rituximab at 12 and 18 months, respectively, compared with 39% and 33% in the control group (P,0.001) (6). Similar remission rates were observed between groups in patients with major renal disease (75% complete remission in the rituximab group versus 76% in the CYC group).…”
Section: Recent Randomized Controlled Trialsmentioning
confidence: 59%
“…In a subgroup analysis, RTX at 6 months was found to be superior to CYC in inducing remission in those who relapsed than CYC in patients enrolled in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial (39). Evaluation over a longer period of time of patients in the RAVE trial with severe AAV found that a single course of RTX was as effective as continuous conventional immunosuppressive therapy for induction and maintenance of remission over an 18-month period (44). RTX also has been used to maintain remission in noncontrolled trials, with promising results in an ongoing randomized controlled trial (40,42).…”
Section: Discussionmentioning
confidence: 99%